Peningkatan aktivitas dan hasil belajar IPS peserta didik dengan menggunakan media pembelajaran “Sipete” - Martina Lona Jusita (Jurnal Teori dan Praksis Pembelajaran IPS, 2018)
Understanding the Subthemes of Nature of Indonesia, especially on sub-theme Flora and Fauna will be more easily understood by learners based on the learning experience gained from the transfer of knowledge submitted by teachers. For that, teachers need to use a medium as an intermediary in learning. The appropriate learning medium is to use "Sipete". It is also expected that the selected learning media can improve the activity and learning outcomes of learners. Based on the results of research proves that the use of learning media "Sipete" can improve the activity and learning outcomes of learners. Evident from each cycle showed a significant improvement. In the first cycle of learning activities, only 15 students (46.88%) showed high learning activity with the percentage of success reached 57 in enough category, increased to 23 people (71,88%) in Cycle II with the success of the action reached 73 in good category. In the third cycle increased to 27 people (84.38%) which showed high learning activity with the percentage of success reached 82 in very good category.DOI: 10.17977/um022v3i12018p013